Two-layered structure of subtidal sediment flux across intertidal mudflats due to tidal surges and surface waves - Zhang, Qianjiang; Wu, Chuangshou; Gu, Weifang; Zhou, Feng (Frontiers in Marine Science, 2025)
Introduction and MethodsField observations were conducted on an intertidal mudflat along the Zhejiang coast to investigate the influence of tidal surges and waves on subtidal sediment flux. This study reveals a two-layer structure in subtidal sediment flux: landward flux occurs above the mid-depth of the water column, while seaward flux is observed in the near-bed layer.ResultsStrong tidal surges were observed at both the beginning and end of tidal cycles, enhancing sediment transport. Wave height and mean wave periods peaked during high tide and decreased during tidal surges. In the water column layers above mid-depth, flood surges with high suspended sediment concentrations (SSC) induced landward sediment flux in the subtidal time scale. In the near-bed layer, SSC exhibited peaks during flood surges, ebb surges, and high tide.DiscussionDuring high tide, upward diffusion of sediment by tidal currents balances the downward sediment setting at the near-bed layer, promoting the accumulation of sediment setting from upper layer. The wave shear stress suspended the seabed sediment during high tide, facilitating the formation of near-bed high SSC. Tidal currents showed shorter durations during the flood phase and longer durations during the ebb phase. The high SSC transported seaward by weak ebb currents during high tide accounted for approximately 30% of the total ebb sediment flux, playing a significant role in offshore subtidal sediment transport. The macrotides and strong wave activity provide suitable condition for the development of the two-layer structure of sediment transport in intertidal mudflats.